Educational Supervision in the Era of Digital Transformation: Concepts, Objectives, and Implications for Teacher Professional Development - Edi Rahmat Hidayat; Sofa, Sofa; Ali Nurhadi (Penerbit Hellow Pustaka, 2025)
The digital transformation has fundamentally reshaped educational supervision, shifting it from conventional inspection-oriented practices to a more collaborative, reflective, and data-driven model. This article aims to analyze the conceptual reconstruction of educational supervision in the digital era, outline its strategic objectives, and examine its implications for teacher professionalism. Employing a library research approach, the study synthesizes insights from approximately 20 national and international journal articles, scholarly books, and official reports related to educational digitalization. The findings reveal three major paradigm shifts: the emergence of data-driven supervision, the strengthening of collaborative and reflective professional cultures, and the development of continuous supervision supported by technological integration. Relevant supervision models include data-driven supervision, e-supervision, and reflective–collaborative–appreciative supervision, all of which collectively enhance teachers’ digital pedagogical competence, reflective capacity, and culture of innovation. Despite these opportunities, digital supervision faces challenges such as uneven digital literacy, technological infrastructure gaps, and limited digital leadership capacity among school leaders. This article concludes that successful implementation of digital supervision requires a digitally ready school ecosystem and visionary leadership, positioning digital supervision as a key driver of teacher professionalism in the era of Education 4.0 and 5.0.